Distal Radius Fracture Surgery with Anatomic Volar Plate in Adolescents and Young Adults - Seppänen, Aleksanteri (My University, 2023)
ABSTRACT Background: Distal radius fractures are the most common fractures among teenagers. In addition to Kirschner wires, after growth plate closure anatomical volar radius plates may also be used for fixation. Current volar plates have been designed to fit the wrist of an average adult patients. The aim of this article is to review the use and the suitability of said plates in the treatment of teenagers. Methods: Retrospective data from patient records was collected on 59 patients, aged from 13 to 19 years, who underwent a plate fixation of distal radius at a tertiary center (level one university trauma hospital). 31 of 59 patients had been operated using an anatomic plate. We reviewed and analyzed patient characteristics, injury mechanisms and types, post-operative complication and pre- and postoperative radiological parameters. Results: 29 wrists were operated using volar and three using a dorsal anatomic plate. Out of the 29 wrists, in 17 (58,6%) wrists the plate positioning corresponded to Soong gr II. In our follow-up period the incidence of the post-operative complications was not greater than reported among adults. The plate was removed post-operatively in two instances. One removal was done due to inadequate plate positioning causing tendon irritation, and the other due to superficial wound infection. No patients under 15 years of age were operated using the anatomic volar plate. Conclusions: We infer that the use of volar locking plates is an applicable treatment method operating distal radius fractures of teenagers with no significant increase in the risk of short-term complications. Further research is required to assess the long- term impact on the flexor tendons and complications.
Keywords: Distal radius fracture, volar plate, locking plate fixation, osteosynthesis, adolescent